Heavy metal contamination, nutritional composition, and health risk assessment of biscuits: A Monte Carlo simulation approach - Tasmina Afroz Chowdhury; A.J.M. Morshed; Md．Samrat Mohay Menul Islam; Md．Ashraful Islam; Dipankar Chakraborty; A K M Samsu Uddin Azad (Food Chemistry Advances)
The purpose of this study was to evaluate the nutritional quality, mineral content, and heavy metals using Atomic Absorption Spectrophotometry (AAS) in different types of biscuits collected from Chattogram. Significant variations were found in the physicochemical parameters (moisture, fat, ash, protein, fiber, and carbohydrate) affecting overall quality and nutritional value. Moisture and ash content were higher than the safety standards in some samples. This highlights the risk of microbial growth and the use of low-grade raw materials. Among minerals, only sodium (Na) exceeded the tolerable daily intake level. Heavy metals were found only in very few samples. Hierarchical Cluster Analysis (HCA) and Principal Component Analysis (PCA) highlighted the differences in the compositional profile. Compositional profile deviations occur as a result of variations in formulation practices and raw materials. The method was validated by performing the Limit of Detection (LOD), the Limit of Quantification (LOQ), and recovery analysis. The Target Hazard Quotient (THQ) was less than one. The Monte Carlo Simulation (MCS) demonstrated negligible non-carcinogenic risks for both adults and children. This study underscores the importance of quality control and regulatory monitoring to safeguard public health.